Jurnal pendidikan Malaysia (Penerbit UKM, Universiti Kebangsaan Malaysia, 2012)
Jurnal Pendidikan Malaysia (Malaysian Journal of Education), formally known as Jurnal Pendidikan, is a refereed journal that publishes original manuscripts covering the entire fields of education. The journal is committed to disseminating of scholarly knowledge and research findings in educational research and development.